Assessing the impact of ventilation systems on indoor air quality: a mock-up experiment in Dubai - Jung, Chuloh; El Samanoudy, Gamal; Alqassimi, Nahla; Sherzad, Mohammed (Frontiers in Built Environment, 2023)
Indoor Air Quality (IAQ) has become an important concern in Dubai, driven by public health awareness, environmental regulations, and government initiatives. The Dubai Municipality has introduced guidelines and standards for IAQ in residential and non-residential buildings, emphasizing ventilation, material selection, and testing protocols. IAQ monitoring and testing are encouraged, and public awareness campaigns educate individuals about IAQ and its impact on health. Green building regulations in Dubai also address IAQ considerations. The Dubai Municipality has comprehensively assessed IAQ in public buildings, leading to stringent regulations. However, research on IAQ improvement and challenges associated with apartment ventilation systems is limited. This study aims to evaluate the IAQ improvement and potential issues of a ventilation system in an apartment through a mock-up experiment. Factors such as air volume, ventilation system type, and supply/exhaust duct configuration are analyzed. The results show that installing a ventilation device with a ventilation rate of 0.3-0.8 times/h reduces Formaldehyde (HCHO) and Volatile Organic Compounds (VOCs) concentrations by 30-50%. The IAQ improvement is not significantly influenced by air volume. Each room supply/exhaust method shows a 10% higher reduction in VOC concentrations than the supply/kitchen exhaust unit method. Preventing backflow and addressing cold drafts are recommended during ventilation system installation. Noise measurements comply with standards in most cases. These findings contribute to developing guidelines for ventilation system design and installation in apartments, promoting healthier indoor environments. Further research with a broader range of ventilation devices and real-world conditions is recommended to validate these findings.